Surface modification of dehydrothermal crosslinked gelatin film using a 50 Hz oxygen glow discharge - Prasertsung, I.; Mongkolnavin, R.; Damrongsakkul, S.; Wong, C.S. (Elsevier, 2010)
In this work, an oxygen glow discharge using AC 50 Hz is used for the treatment of type A gelatin film crosslinked by dehydrothermal (DHT) process. The effects of plasma on the properties of gelatin films are investigated. The operating discharge power, pressure and gas flow rate are varied in the range of 3-12 W. 0.4-2 mbar and 3-10 sccm, respectively. The effects of ageing time and temperature on the surface properties of plasma-treated gelatin are also investigated. The results show that the water contact angle of crosslinked gelatin treated by oxygen plasma is lower than that of untreated crosslinked gelatin film. This implies that the oxygen plasma is able to introduce hydrophilic groups onto the surface of the crosslinked gelatin. The efficiency of the surface treatment is increased by increasing the discharge power, increasing the pressure and decreasing the oxygen gas flow rate. The results on atomic force microscopy (AFM) reveal that the surface roughness of the plasma-treated gelatin film is enhanced by increasing the treatment period. The results on ageing tests indicate that at low ageing temperature, the surface properties of plasma-treated gelatin films can be maintained for a longer period as compared to those stored at higher temperature. The change in hydrophilicity during the ageing process is mainly due to the recovery of surface chemistry, not surface roughness. It may be concluded that the AC 50 Hz plasma system can be used effectively to manipulate the surface properties of crosslinked gelatin films. (C) 2010 Elsevier B.V. All rights reserved.